Struktur Tiga Babak : Pendekatan Naratif Dalam Penulisan Naskah Video Feature “Beauty After Life” - Assyivha Nesya Putri Aditiya; Kokom Komariah; Fajar Syuderajat (Pusat Riset dan Inovasi Nasional, 2025)
“Beauty After Life” is a video feature that addresses the issue of expired cosmetic waste that can be donated to mortuary makeup artists. The topic emerged from concerns over the growing consumerism in cosmetic products. This study aims to explain the implementation of the Three-Act Structure in the scriptwriting process of the video feature. The Three-Act Structure is used as a narrative framework to build emotional engagement and deliver messages clearly and effectively. The script is developed using a human interest feature approach that emphasizes real-life experiences and evokes audience empathy. This creation of work uses a descriptive-analytical method with a qualitative approach, focusing on the stages of pre-production, script development, and narrative composition. Each act is analyzed based on its contribution to the story's flow and thematic coherence. The first act introduces the issue, the second act develops the conflict through data and interviews, and the third act provides a reflective conclusion along with proposed solutions. This structure not only supports the smooth progression of the narrative but also ensures that both moral and emotional messages are conveyed to the audience. The results show that applying the Three-Act Structure enhances audience understanding, emotional engagement, and awareness of the social issue presented. The use of the Three-Act Structure in writing a human interest video feature script is effective in building a cohesive narrative and supporting social advocacy.